Justice 2.0: Street harassment victims’ use of social media and online activism as sites of informal justice - Fileborn, Bianca (The British Journal of Criminology, 2017)
Emerging scholarship has considered the potential for online spaces to function as sites of informal justice. To date, there has been little consideration of the experiences of individuals who seek justice online, and the extent to which victims’ justice needs can be met online. Drawing on the findings of a mixed-methods research project with street harassment victims in Melbourne, Australia, I consider participants’ reasons for, and experiences of, disclosing their encounters of street harassment online. I examine the extent to which these ‘map on to’ a selection of victim’s justice needs. While it is evident that online spaces can function as sites of justice, it is vital to ask for whom and in which contexts justice can be achieved online.

Sex and the City: Exploring Young Women's Perceptions and Experiences of Unwanted Sexual Attention in Licensed Venues - Fileborn, Bianca (Current Issues in Criminal Justice, 2012)
Recent research has highlighted the need to explore how specific social contexts influence the occurrence of sexual violence and sexually harassing behaviours. This article considers the occurrence of unwanted sexual attention towards young women within the social context of licensed venues in Melbourne, Victoria. Using focus group data from a small qualitative study, three ‘characteristics’ of unwanted sexual attention are considered: the forms this behaviour takes and how it impacts young women; the nature of the relationship between victim and perpetrator; and the role of venue culture in facilitating this behaviour. It is argued throughout this article that an intersection of broader social norms and the specific social norms and cultural mores of licensed venues creates a social environment that can facilitate the occurrence of unwanted sexual attention, and that restrains the ways in which young women are able to respond to these experiences.
Keywords: Camille